Inhaled Lavender Aromatherapy for Preoperative Anxiety: A Systematic Review of Randomized Controlled Trials - Gita Al-Fauzia Salsabilla; Arina Maliya (STIKep PPNI Jawa Barat, 2026)
Background: Preoperative anxiety is common among patients undergoing surgery and may adversely affect perioperative outcomes, including hemodynamic instability, increased anesthetic requirements, and delayed recovery. Lavender aromatherapy has been widely used as a complementary non-pharmacological intervention; however, its effectiveness in preoperative care remains variably reported across studies. Objective: This review aimed to synthesize evidence from randomized controlled trials (RCTs) on the effectiveness of inhaled lavender aromatherapy in reducing preoperative anxiety among adult surgical patients. Methods: A structured review of RCTs was conducted using Scopus, PubMed, and ScienceDirect. Studies published within the last 10 years were searched using combinations of terms related to lavender aromatherapy, inhalation, and preoperative anxiety. Eligibility criteria were defined using the PICOS framework. After duplicate removal, title and abstract screening, and full-text assessment, 11 RCTs were included in the final qualitative synthesis. Due to heterogeneity in surgical populations, intervention protocols, comparators, and anxiety measurement tools, findings were synthesized narratively. Results: Eleven RCTs met the inclusion criteria. Most studies reported reductions in preoperative anxiety following inhaled lavender aromatherapy compared with standard care, no-aroma control, or placebo. Several trials also reported additional benefits, such as improved hemodynamic parameters, reduced cortisol levels, and lower anesthetic requirements. However, the findings were not entirely consistent, as some studies found lavender to be comparable to other non-pharmacological interventions or not significantly different from placebo. Conclusion: Inhaled lavender aromatherapy appears to be a promising complementary intervention for reducing preoperative anxiety in adult surgical patients. Nevertheless, the evidence remains heterogeneous, and effectiveness may vary according to clinical context, comparator type, and intervention protocol. Further high-quality trials using standardized administration methods and outcome measures are needed to clarify its clinical role.